Improvement of Lay Up Shoot Learning Outcomes in Basketball Learning with Deer Jumping Game - Furyanti, Erya; Kristina, Putri Cicilia; Handayani, Widya (Perkumpulan Program Studi Doktor Pendidikan (PPSDP), 2024)
This study investigates the effectiveness of using the Deer Jump game to improve Lay-Up Shoot skills in physical education lessons for seventh-grade students at SMP Negeri 2 Pagar Alam. Conducted as classroom action research, the study was implemented over two cycles, each consisting of one meeting. The research subjects were all 30 students in class VII A, which included 14 boys and 16 girls. Data collection involved multiple instruments: an observation sheet to monitor student engagement and performance, interview guidelines for gathering qualitative feedback, and field notes to record contextual observations. The data were analyzed and presented descriptively to evaluate the impact of the intervention. The findings indicate that incorporating the Deer Jump game significantly enhanced both the learning process and outcomes for Lay-Up Shoot skills. Specifically, the average student score improved from 61.2 before the intervention to 76.1 in the first cycle, and further increased to 85.03 in the second cycle. Notably, by the end of the second cycle, 88.46% of the students met or exceeded the minimum competency standard of 70, demonstrating the effectiveness of the game-based approach in achieving higher levels of student performance and skill development.